Sickness Absence and Disability Pension in the Very Long Term: A Finnish Register-Based Study With 20 Years Follow-Up - Klein, Julia; Reini, Kaarina; Saarela, Jan (Frontiers in Public Health, 2021)
Although sickness allowance is paid for short-term sickness absence, it is associated with a heightened risk of receiving disability pension in the future. Using event history analysis, we examined the long-term risk of disability pension receipt after first-time receipt of medically certified sickness allowance in every single year after sickness allowance was first recorded with longitudinal data from the Finnish population-register spanning 1989-2010. We observed 110,675 individuals aged 16-40 years at baseline. Using discrete-time hazard models, we estimated how first-time receipt of sickness allowance affected the probability of receiving disability pension in the very long term. Average follow-up time was 20.6 years. During follow-up, 40 percent received sickness allowance and 10 percent received disability pension. In the first years after sickness allowance receipt, there was a substantial difference between long-term and short-term sickness allowance recipients in the hazard of becoming a disability pensioner. This difference levelled out over time, but even 20 years after first sickness allowance receipt, the hazard of disability retirement was more than 15 times higher than that of non-recipients. Patterns were similar for men and women. First-time receipt of SA is a powerful predictor for disability pension receipt, also in the very distant future. Thus, it can be used to monitor people with heightened risk of becoming more permanently ill and falling outside the labour market.